2017
DOI: 10.1111/eip.12531
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of remission during acute treatment of first‐episode schizophrenia patients involuntarily hospitalized and treated with algorithm‐based pharmacotherapy: Secondary analysis of an observational study

Abstract: The importance of early intervention and specific and adequate treatments of negative symptoms is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
(81 reference statements)
1
4
0
Order By: Relevance
“…Other predictors of non-response and resistance in this study were the younger age of onset and the diagnosis of schizophrenia. Yoshimura et al (76) confirmed the previous results about the influence of negative symptoms on resistance in 131 patients with schizophrenia. Investigation conducted by Downs et al (77) in 638 subjects with early-onset psychosis highlighted the importance of the negative symptomatology in predicting response also in particular populations such as children and adolescents.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Other predictors of non-response and resistance in this study were the younger age of onset and the diagnosis of schizophrenia. Yoshimura et al (76) confirmed the previous results about the influence of negative symptoms on resistance in 131 patients with schizophrenia. Investigation conducted by Downs et al (77) in 638 subjects with early-onset psychosis highlighted the importance of the negative symptomatology in predicting response also in particular populations such as children and adolescents.…”
Section: Resultssupporting
confidence: 61%
“…In line with previous findings, Demjaha et al (8) reported that longer DUP predicted treatment resistance. Moreover, Yoshimura et al (76) found that a shorter DUP predicted favorable response and remission in FEP patients with schizophrenia.…”
Section: Resultsmentioning
confidence: 99%
“…As in previous studies (Chan et al, 2021;Díaz et al, 2013;Friis et al, 2016;Lally et al, 2016;Smart et al, 2021), earlier age of onset of psychosis, poor premorbid adjustment, low educational level, being male and being single were identified as risk factors in clinical treatment resistance, although the effect of gender on treatment resistance has not been confirmed in other studies (Crespo-Facorro et al, 2013a;A Demjaha et al, 2017;Wimberley et al, 2016). In terms of clinical predictors, higher severity negative symptoms on FEP had also been associated with higher rates of resistance to treatment (Bozzatello et al, 2019;A Demjaha et al, 2017;Yoshimura et al, 2017). These findings, in line with previous studies, suggest that treatment-resistant schizophrenia could be a different subtype of schizophrenia.…”
Section: Discussionmentioning
confidence: 71%
“…We excluded 8061 at title and abstract level. A total of 212 articles were reviewed at full-text level, with 12 studies meeting the criteria for inclusion, [20][21][22][23][24][25][26][27][28][29][30][31] of which one was an unpublished data-set. 28 No additional studies were identified through hand-searching.…”
Section: Study Selectionmentioning
confidence: 99%
“…Nine studies used prospective data collection, with the other three being collected retrospectively. Only two studies provided data on involuntary treatment status, 21,31 precluding meaningful sensitivity analysis on this variable.…”
Section: Study Characteristicsmentioning
confidence: 99%